Mesh Processing in Medical Image Analysis 2012 MICCAI 2012 International Workshop, MeshMed 2012, Nice, France, October 1, 2012, Proceedings - Levine, Joshua A.; Paulsen, Rasmus R.; Zhang, Yongjie (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2012)
This book constitutes the refereed proceedings of the International Workshop on Mesh Processing in Medical Image Analysis, MeshMed 2012, held in Nice, France, in October 2012 in conjunction with MICCAI 2012, the 15th International Conference on Medical Image Computing and Computer Assisted Intervention. The book includes 16 submissions, 8 were selected for presentation along with the 3 plenary talks representative of the meshing, and 8 were selected for poster presentations. The papers cover a broad range of topics, including statistical shape analysis and atlas construction, novel meshing approaches, soft tissue simulation, quad dominant meshing and mesh based shape descriptors. The described techniques were applied to a variety of medical data including cortical bones, ear canals, cerebral aneurysms and vascular structures.